Numerical verification on formability of metallic alloys for skin structure using multi-point die-less forming - Abebe, Misganaw; Park, Ji-Woo; Kim, Jeong; Kang, Beom-Soo (International journal of precision engineering and manufacturing, 2017)
Recently, a trend towards lightweight components in the automobile and aircraft industries has developed as one of the primary paths to improve the fuel consumption rate and reduce environmental pollution. Therefore, various sheet materials such as composite and fiber reinforced metal laminates, and metallic alloys are used to satisfy this trend. However, to ensure good impact performance of the automotive structural components and to reduce the production cost, metallic alloy sheets are thought to be the most attractive for sheet blank materials. In this study, the formability of the selected metallic alloys sheet materials such as AA3003-H14, AZ31B, DP600, is investigated on multi-point dieless forming (MDF). For verifying the formability, wrinkling and dimple occurrence, a limit index is newly proposed for convex and saddle target shapes based on: cushion thickness, curvature radius, bank thickness, and punch stroke. Numerical simulations are performed on ABAQUS commercial software with consideration of the springback behavior. An ordinary Kriging model prediction technique is applied to replace the computationally expensive finite element simulation to find the wrinkling and dimple occurrence limit. For forming limit index validation, one optimal case is conducted, and the simulation and experimental result show the product is wrinkling and dimpling free.